Unsur Maritim Bali Utara: Refleksi Sastrawi Teks Babad Buleleng - Pande Putu Abdi Jaya Prawira; I Nyoman Darma Putra; I Wayan Pastika (PURBAWIDYA, 2025)
This article examines the elements of maritime literature in the locality of North Bali, based on the source Babad Buleleng. Babad Buleleng chronicles the early dynasty of kings who ruled the Buleleng region. Buleleng is a strategic area in North Bali and has often been involved in economic, political, and multicultural interactions. This paper uses a textual study approach with an interpretive method. Based on the study conducted, it was found that maritime values are deeply embedded in Babad Buleleng. The identified aspects include navigation, trade, cultural contacts and maritime safety. These aspects have influenced the socio-cultural life of the community until today. Through these maritime aspects, it can be stated that Buleleng has been a strong maritime locus in Bali in the past. This value can be optimized to build maritime awareness and identity of Bali's maritime people, especially in North Bali, to reposition the sea as an important axis in the economic and socio-cultural life of the community, based on the wisdom of classical literary works inherited to this day.